2004
DOI: 10.1128/jb.186.16.5311-5320.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Cytolysin A (ClyA) in Pathogenic Escherichia coli Strains

Abstract: Cytolysin A (ClyA) of Escherichia coli is a pore-forming hemolytic protein encoded by the clyA (hlyE, sheA) gene that was first identified in E. coli K-12. In this study we examined various clinical E. coli isolates with regard to the presence and integrity of clyA. PCR and DNA sequence analyses demonstrated that 19 of 23 tested Shiga toxin-producing E. coli (STEC) strains, all 7 tested enteroinvasive E. coli (EIEC) strains, 6 of 8 enteroaggregative E. coli (EAEC) strains, and 4 of 7 tested enterotoxigenic E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 50 publications
1
102
0
Order By: Relevance
“…By comparative genomic hybridization, serovars Montevideo, Oranienfoburg, Sendai and Muenchen were also shown to possess these genes, although only one strain per serovar was tested (Porwollik et al, 2004). The presence of clyA, by itself, has been observed in E. coli, in both pathogenic and K-12 strains (Ludwig et al, 2004). BLAST analysis with the nucleotide sequence revealed that clyA is also present in Shigella flexneri serotypes 2a and 5.…”
Section: Resultsmentioning
confidence: 98%
“…By comparative genomic hybridization, serovars Montevideo, Oranienfoburg, Sendai and Muenchen were also shown to possess these genes, although only one strain per serovar was tested (Porwollik et al, 2004). The presence of clyA, by itself, has been observed in E. coli, in both pathogenic and K-12 strains (Ludwig et al, 2004). BLAST analysis with the nucleotide sequence revealed that clyA is also present in Shigella flexneri serotypes 2a and 5.…”
Section: Resultsmentioning
confidence: 98%
“…It is also present in enteropathogenic E. coli (Ludwig et al, 2004), Shigella flexneri (Wallace et al, 2000) and Salmonella enterica serovars Typhi and Paratyphi A (Oscarsson et al, 2002). ClyA is haemolytic and causes LDH release in nucleated cells (delCastillo et al, 1997;Oscarsson et al, 1996Oscarsson et al, , 1999, which has led to the suggestion that it too mediates osmotic lysis through the formation of transmembrane homo-oligomeric pores (Eifler et al, 2006;Tzokov et al, 2006;Wallace et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…-hemolysin is a pore-forming cytolysin causing cells to swell and eventually burst [21]. Even though the hemolysis traits of E. coli isolates have been used as presumptive evidence of virulence, the pathogenesis involves exotoxinmediated secretion into the gut lumen [3,26,33].…”
Section: Discussionmentioning
confidence: 99%